Perbedaan Kemampuan Pemahaman Matematis Mahasiswa dengan Menggunakan Strategi Blended Learning dan Strategi Offline Learning di Universitas Pamulang - Noviana, Widyah; Handayani, Ita (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to find out whether there is a difference between students who are treated using blended learning strategies and students who are treated using offline learning strategies. This research was carried out at Pamulang University. The research method used is a quantitative approach with the quasy experimental method. Samples were taken by cluster random sampling. The sample was taken as many as 50 students consisting of 25 students in the experimental class and 25 students in the control class. Instrument tests are validity tests and reliability tests. The validity test uses the product moment formula, and the results are all valid while the reliability test uses the alpha formula and reliable results are obtained. The data collection technique used in this study is in the form of the results of the students' mathematical comprehension ability test. Data analysis using a non-parametric test using the Mann-Whitney Test The results of the data analysis showed that the significance value was 0.015<0.05 so that there was a significant difference between the class that was given the blended learning strategy treatment and the class that was given the offline learning strategy treatment